Survey on schizophrenia treatment in Mexico: perception and antipsychotic prescription patterns - Apiquian, Rogelio (BioMed Central, 2004)
BACKGROUND: Since the introduction of antipsychotics, especially the so called atypicals, the treatment of schizophrenia has shown important improvements. At the present time, it is preferred to label clozapine and other antipsychotics sharing similar profiles as second-generation antipsychotics (SGAs). These medications have been proposed by some experts as a first line treatment for schizophrenia. It is critical to have reliable data about antipsychotic prescription in Mexico and to create management guidelines based on expert meetings and not only on studies carried out by the pharmaceutical industry. Only this approach will help to make the right decisions for the treatment of schizophrenia. METHODS: A translated version of Rabinowitz's survey was used to evaluate antipsychotic prescription preferences and patterns in Mexican psychiatrists. The survey questionnaire was sent by mail to 200 psychiatrists from public institutions and private practice in Mexico City and Guadalajara, Mexico. RESULTS: Recommendations for antipsychotics daily doses at different stages of the treatment of schizophrenia varied widely. Haloperidol was considered as the first choice for the treatment of positive symptoms. On the contrary, risperidone was the first option for negative symptoms. For a patient with a high susceptibility for developing extrapyramidal symptoms (EPS), risperidone was the first choice. It was also considered that SGAs had advantages over typical antipsychotics in the management of negative symptoms, cognitive impairment and fewer EPS. Besides, there was a clear tendency for prescribing typical antipsychotics at higher doses than recommended and inadequate doses for the atypical ones. CONCLUSIONS: Some of the obstacles for the prescription of SGAs include their high cost, deficient knowledge about their indications and dosage, the perception of their being less efficient for the treatment of positive symptoms and the resistance of some Mexican physicians to change their prescription pattern. It is necessary to reach a consensus, in order to establish and standardize the treatment of schizophrenia, based on the information reported in clinical trials and prevailing economic conditions in Mexico.